Ultrafast spin-polarized electron dynamics in the unoccupied topological surface state of Bi2Se3. (22nd June 2017) - Bugini, D; Boschini, F; Hedayat, H; Yi, H; Chen, C; Zhou, X; Manzoni, C; Dallera, C; Cerullo, G; Carpene, E
Abstract: The three-dimensional topological insulator Bi2 Se3 presents two cone-like dispersive topological surface states centered at the Γ ̄ point. One of them is unoccupied in equilibrium conditions and located 1.8 eV above the other one lying close to the Fermi level. In this work we employ time- and angle-resolved photoemission spectroscopy with circularly polarized pump photons to selectively track the spin dynamics of the empty topological states. We observe that spin-polarized electrons flow along the topological cone and recombine towards the unpolarized bulk states on a timescale of few tens of femtoseconds. This provides direct evidence of the capability to trigger a spin current with circularly polarized light.